Self Control and Self Efficacy Increase Mother’s Birth Labor Satisfaction - Agustine Ramie; Yati Afiyanti; Hening Pujasari (Universitas Airlangga, 2014)
Introduction: Self-control and self-effi cacy are necessary for would-be mothers to enhance their birth labor satisfaction. This research was conducted in Ratu Zalecha public hospital in Martapura and in Banjarbaru public hospital in South Borneo with the aim to identify the relationship between self-control and self effi cacy on the one hand, and birth labor satisfaction on the other hand.Methods: Cross-sectional approach with correlative analysis was applied for this research, using 125 samples chosen from normal childbirth using consecutive sampling techniques. Results: The result of Chi-Square correlation test showed that there were some relationships between self-control as well as self-effi cacy and birth labor satisfaction (ρ value 0.002,α: 0.05) and (ρ value 0.000, α: 0.05). There were four variables resulted from double logistic analytical regression that play signifi cant roles in birth labor satisfaction, i.e., self-control, self-effi cacy, family income, and parity.Conclusion: The most infl uencing variable in birth labor satisfaction was family income. Labor carers should provide enough support so that would-be mothers can view the process of childbirth as a positive and pleasant experience; hence, birth labor satisfaction will surely be tremendous.Keywords: birth labor satisfaction, self-control, self-effi cacy